Evaluation of [Ln(H2cmp)(H2O)] metal organic framework materials for potential application as magnetic resonance imaging contrast agents - Pereira, Giovannia A; Peters, Joop A; Paz, Filipe A Almeida; Rocha, João; Geraldes, Carlos F G C (Inorganic chemistry, 2010)
Aqueous suspensions of metal organic frameworks (MOF) containing different Ln(3+) ions, consisting of a series of layered Ln(3+) networks formulated as [Ln(H(2)cmp)(H(2)O)] (where H(5)cmp is (carboxymethyl)iminodi(methylphosphonic acid), with a relatively wide size distribution (400 nm to 1 microm) were studied by relaxometry. The water (1)H longitudinal (r(1)) and transverse (r(2)) relaxivities were obtained for aqueous suspensions of these materials with different lanthanide ions. The values of r(1) are very small and varied only slightly with the effective magnetic moment (mu(eff)) of the lanthanide ions, while r(2) values are larger and proportional to the value of mu(eff)(2). The dependence of R(2) on tau(CP) (the time interval between two consecutive refocusing pulses in the train of 180 degrees pulses applied in a CPMG pulse sequence) was evaluated. The value of R(2) initially increases with tau(CP) and then saturates at higher tau(CP) at a value that is about 3 to 5 times lower than R(2p)*. This can be explained by the static dephasing regime (SDR) theory, in which the diffusion effect is taken into account and where the condition tau(D) > Delta omega(r(p))(-1) holds (tau(D) = r(p)(2)/D, where D is the diffusion coefficient, r(p) is the radius of the particle, and Delta omega(r(p)) is the Larmor frequency shift at the particle's surface). Separation of the particles into two fractions with different particle sizes led to a significant enhancement of the r(2) relaxivity of the smaller particles with a narrow size distribution. Magnetometric measurements performed with the particles containing Dy(III), Ho(III), and Gd(III) showed a typical paramagnetic behavior from 4 to 100 K, used to determine the Curie constants.